Epidemiological and Clinical Findings of Short-Term Recurrence of Severe Acute Respiratory Syndrome Coronavirus 2 Ribonucleic Acid Polymerase Chain Reaction Positivity in 1282 Discharged Coronavirus Disease 2019 Cases: A Multicenter, Retrospective, Observational Study. (13th September 2020) - Chen, Sheng-Long; Xu, Hui; Feng, Hui-Ying; Sun, Jiu-Feng; Li, Xin; Zhou, Lin; Song, Wen-Liang; Huang, Shan-Shan; He, Jun-Lei; Deng, Yi-Yu; Wang, Rui-Jie; Fang, Ming
Abstract: Background: Short-term recurrence of positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ribonucleic acid (RNA) polymerase chain reaction (PCR) in discharged coronavirus disease 2019 (COVID-19) patients attracts the public's concern. This study aimed to determine the clinical and epidemiological results of such patients. Methods: This retrospective study was conducted on 32 designated hospitals for COVID-19 patients discharged from January 14 to March 10, 2020. After 28-day followed-up, patients who tested positive again for SARS-CoV-2 RNA and confirmed by reverse-transcriptase polymerase chain reaction were re-admitted to hospital for further treatments. All of the close contacts of patients who tested positive again were asked to self-segregate for 14 days. Data of epidemiology, symptoms, laboratory tests, and treatments were analyzed in those patients, and their close contacts were investigated. Results: Of 1282 discharged patients, 189 (14.74%) tested positive again for SARS-CoV-2 RNA during 28-day follow-up. The median time from discharge to the next positive test was 8 days (interquartile range [IQR], 5–13). Patients in the group that tested positive again were younger (34 vs 45 years, P < .001) with a higher proportion of moderate symptoms (95.77% vs 84.35%, P < .001) in the first hospitalization than in the negative group. During the second hospitalization, all patients who tested positive again showed normal peripheral white blood cells and lymphocytes and no new symptoms of COVID-19; 78.31% further improved on chest computed tomography scan compared with the first discharge, yet 25.93% accepted antiviral therapy. The median time of re-positive to negative test was 8 days (IQR, 4–15). None of the close contacts developed COVID-19. Conclusions: Our data suggest that the short-term recurrence of positive SARS-CoV-2 RNA in discharged patients is not a relapse of COVID-19, and the risk of onward transmission is very low. This provides important information for managing COVID-19 patients. Abstract : In this multicenter study involving 1282 discharged COVID-19 patients with 28-day follow-up, 14.74% tested positive again for SARS-CoV-2 RNA. However, our data suggest that re-positive is not a relapse of COVID-19, and the risk of onward transmission is very low.